2007
DOI: 10.3122/jabfm.2007.04.060118
|View full text |Cite
|
Sign up to set email alerts
|

Children and Firearms in the Home: A Southwestern Ohio Ambulatory Research Network (SOAR-Net) Study

Abstract: Background:To ascertain the prevalence of gun ownership, gun safety education, and parental attitudes on gun counseling in a Midwestern sample.Methods: Parents seeking care at participating practices in the Southwestern Ohio Ambulatory Research Network were recruited to complete a survey about gun ownership, gun safety education, and gun counseling attitudes. Attitudes and beliefs were compared between gun owners and non-gun owners.Results: Twenty-four percent of respondents had at least 1 gun in the home. Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This finding may be due to the infrequency with which patients in our study who were suffering from a psychiatric disorder (but whose actions had not escalated to the threshold of a suicide attempt) received counselling in a medical setting to remove firearms from their homes, a possibility consistent with findings in previous work but to which our data do not speak 31 32…”
Section: Discussionsupporting
confidence: 83%
“…This finding may be due to the infrequency with which patients in our study who were suffering from a psychiatric disorder (but whose actions had not escalated to the threshold of a suicide attempt) received counselling in a medical setting to remove firearms from their homes, a possibility consistent with findings in previous work but to which our data do not speak 31 32…”
Section: Discussionsupporting
confidence: 83%
“…Firearms are present in the homes of between one fifth and one third of American children and adolescents (DuRant et al, 2007; Forbis et al, 2007; Schuster, Franke, Bastian, Sor, & Halfon, 2000; Sorenson & Vittes, 2004). Analyzing data from the 1994 National Health Interview Survey and its Year 2000 objectives supplement, Schuster and colleagues found that 35% of homes with children younger than age 18 years contained at least one firearm (Schuster et al, 2000); more recently, Coyne-Beasley, Miles, Lees, Proescholdbell, and Ford (2012) reported that 40% of North Carolina homes with children between the ages 0 and 18 surveyed in 2008 contained at least one firearm.…”
mentioning
confidence: 99%
“…The 29-item self-report questionnaire, developed by the study team, was based on the literature and previous instruments (with permission),[7, 8] and was modified after review by participating physicians and pilot testing with 7 mothers. Parents were asked if they thought pediatricians should inquire about household firearms, provide safe storage advice, and selected from a list of options to indicate their reaction to advice from a pediatrician not to have firearms in the house for child safety.…”
Section: Methodsmentioning
confidence: 99%